Comparison of Long-Term and Perioperative Outcomes of Robotic Versus Conventional Laparoscopic Gastrectomy for Gastric Cancer: A Systematic Review and Meta-Analysis of PSM and RCT Studies - Feng, Qingbo; Ma, Hexing; Qiu, Jie; Du, Yan; Zhang, Guodong; Li, Ping; Wen, Kunming; Xie, Ming (Frontiers in Oncology, 2021)
Background To investigate the perioperative and oncological outcomes of gastric cancer (GC) after robotic versus laparoscopic gastrectomy (RG versus LG), we carried out a meta-analysis of propensity score matching (PSM) studies and randomized controlled study (RCT) to compare the safety and overall effect of RG to LG for patients with GC. Methods PubMed, Web of Science, EMBASE, and Cochrane Central Register were searched based on a defined search strategy to identify eligible PSM and RCT studies before July 2021. Data on perioperative and oncological outcomes were subjected to meta-analysis. Results Overall, we identified 19 PSM studies and 1 RCT of RG versus LG, enrolling a total of 13,446 patients (6,173 and 7,273 patients underwent RG and LG, respectively). The present meta-analysis revealed nonsignificant differences in tumor size, proximal resection margin distance, distal resection margin distance, abdominal bleeding, ileus, anastomosis site leakage, duodenal stump leakage rate, conversion rate, reoperation, overall survival rate, and long-term recurrence-free survival rate between the two groups. Alternatively, comparing RG with LG, RG has a longer operative time (p < 0.00001), less blood loss (p <0.0001), earlier time to first flatus (p = 0.0003), earlier time to oral intake (p = 0.0001), shorter length of stay (p = 0.0001), less major complications (p = 0.0001), lower overall complications (p = 0.0003), more retrieved lymph nodes (P < 0.0001), and more cost (p < 0.00001). Conclusions In terms of oncological adequacy and safety, RG is a feasible and effective treatment strategy for gastric cancer but takes more cost in comparison with LG.